La estructura del conocimiento práctico - Lorenzano, César (Revista de Filosofía, 2005)
The claim of this article is that the human behavior implies a knowledge of the world –a know how– that can be explained only if we think that the epistemic self is in the possession of a sort of practical theories, structured by a behavior level and a level of practical and perceptive dispositions that generates the actions. The motors of these actions are also analyzed, as well as the relations between the practical and the propositional knowledge.